ALICE project: approach, outcomes ...and the future - Umberto Margiotta; Juliana Raffaghelli (Pensa MultiMedia, 2014)
This article introduces the ALICE (Adults Learning for Intergenerational Creative Experiences) project approach, its main results and a reflection on its contribution to the EU policies. The ALICE project introduced the concept of creative languages (art, digital storytelling, social media) as instrument to build rich and caring environments for children to grow up. As an expected result, the adults' reflection on their own role as educators through intergenerational learning could be stimulated, with impact on the achievement of adults key competences for lifelong learning 1, 4, 5, 7 and 8 (European Commission, 2007) for the participating adults. Children are not direct beneficiaries of the project's approach: however, we can expect that the adults' improvement with regard to the above mentioned Key Competences, will encompass better life conditions for the children.